Tanzania : Joint Staff Assessment of the Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2004)
This paper presents the Joint Staff Assessment of Tanzania's Poverty Reduction Strategy Paper (PRSP) Progress Report. Despite a drought, real economic growth is estimated to have been about 5 percent, sound macroeconomic management was maintained, and notable progress was made in the areas of education and financial sector reform, among others. The report illustrates a number of emerging weaknesses in the Poverty Reduction Strategy process, pointing to areas for attention in the main update. Foremost among them are the need to link the technical-level reviews with a more policy-based debate on sector strategies.